A study of milk production as it affects lamb growth in Romney and Cheviot crossbred sheep : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science of the University of New Zealand - Roberts, Euan Maurice (Massey University, 1952)
Romney and Cheviot Threequarter bred 6 year old ewes, all with twin lambs, were found to produce similar quantities of milk in a 12 week lactation. The Cheviot halfbred ewes produced less milk than either the Romney or 3/4 Cheviot ewes but the disadvantage was not thought to be of an hereitary nature. Both Cheviot groups of ewes gave significantly richer milk than the Romney group. When mated to Southdown rams the ewes of the Romney and each Cheviot breed produced lambs which made similar liveweight gains.
Keywords: Milk yield; Romney Marsh sheep; Cheviot sheep; Sheep growth